Pengaruh Supervisi Akademik dan Ketahanmalangan Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar Negeri Sekecamatan Seberang Ulu 1 Palembang - Nurhasanah Nurhasanah; Dessy Wardiah; Andi Rahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify and analyze: (1) The effect of academic supervision on teacher performance; (2) The effect of principal resilience on teacher performance; and (3) The combined effect of academic supervision and principal resilience on teacher performance. This study is a quantitative research using the partial correlation method. The research was conducted in 13 public elementary schools in the Seberang Ulu 1 District of Palembang, with 163 teacher respondents. Data collection techniques included questionnaires, observation, and documentation. Validity and reliability tests used internal validity and reliability measures. Prerequisite tests for analysis included normality tests, linearity tests, and multicollinearity tests, and the data were analyzed using simple regression and multiple regression techniques. The results of the study showed that: (1) there is a positive and significant effect of academic supervision on teacher performance with a correlation value of 1.296 and a relationship percentage of 0.46%; (2) there is a positive and significant effect of principal resilience on teacher performance with a correlation value of 1.473 and a relationship percentage of 14.186%; and (3) there is a positive and significant combined effect of academic supervision and principal resilience on teacher performance with a correlation value of 3.050 and a relationship percentage of 63.902%. Keywords: Academic Supervision; Resilience; Teacher Performance